Diagnosis of nonstationary processes using reduced interference time-frequency distribution - Koh, Christopher Kok Hwee. (2008)
This project is focused on the application of the start-of-the-art signal processing techniques to the biomedical applications: diagnostics of TMD (Temporomandibular Joint Disorder). This report starts with the background of the time frequency analysis, followed by the detailed investigation of time frequency properties, which served as the basis of our signal processing algorithms.